Optimization of the epoxidation process parameters of fatty acid methyl esters using response surface methodology (RSM) based on central composite design (CCD) / Aishah Derahman and Zurina Zainal Abidin - Derahman, Aishah; Zainal Abidin, Zurina (Universiti Teknologi MARA (UiTM), 2022)
The aim of this study was to apply the experimental design methodology in the optimization of the epoxidation of fatty acid methyl esters (FAME) derived from Jatropha oil. This experiment was carried out with peracetic acid generated in situ by using hydrogen peroxide and acetic acid. The reaction surface (RSM) methodology based on the central composite design (CCD) approach is applied, which involves the percentage (%) of the epoxidation yield as the reaction variables. The reactions were described as the function of parameters such as temperature (50-80 °C), mol ratio of hydrogen peroxide (HP) to unsaturation (1.1-2 mol), mol ratio of acetic acid (AA) to unsaturation (0.5-0.8 mol) and time (2-7 hours). The optimum percentage of epoxidation yield (90.98 %) was at the condition of 65 °C reaction temperature, HP to unsaturation mol ratio of 2.19, AA to unsaturation mol ratio of 0.65 for 6 hours. The formation of epoxides product (oxirane) was confirmed using Fourier transform infrared spectroscopy oxirane peaks (doublet) at 825 and 843 cm-1. The result showed good agreement with the predicted values from the RSM model.